Comparing the Effectiveness of Intranasal Desmopressin and Doxazosin in Men with Nocturia: A Pilot Randomized Clinical Trial - Ceylan, Cavit; Ceylan, Taner; Doluoglu, Omer Gokhan; Yuksel, Selcen; Agras, Koray (Urology Journal, 2013)
Purpose: We aimed to compare the effectiveness of intranasal desmopressin and doxazosin treatments in patients with nocturia and benign prostatic hyperplasia (BPH). Material and Methods: Thirty one men with BPH and three or more episodes of nocturia were randomized to receive 2 mg doxazosin at night for two weeks increasing to 4 mg for a further two weeks versus 20 μg intranasal desmopressin at night. For all patients, number of nocturia, urinary flow rate, residual urine volume and quality of life score were checked. Outcomes were measured at two months. The comparison of before and after treatment changes between the groups were done by student’s t-test. Results: In doxazosin group, mean number of nocturia were 3.2 ± 0.4 (3-4 times) times per night and 1.2 ± 0.8 (0-3 times) times per night before and after treatment, respectively. In desmopressin group, mean number of nocturia were 3.4 ± 0.5 (3-4 times) and 1.5 ± 0.6 (1-3 times) times per night before and after treatment, respectively. In doxazosin group, mean residual urine volumes were 44.3 ± 35.9 ml (range 0-120 ml) and 23.1 ± 18.8 ml (range 0-50 ml) before and after treatment, respectively. In desmopressin group, mean residual urine volumes were 36.6 ± 32.4 ml (range 0-120 ml) and 14.0 ± 26.9 ml (range 0-90 ml) before and after treatment, respectively. Improvements in number of nocturia, residual urine volume, quality of life scores and peak urinary flow rates weren’t statistically significant between two groups, whereas change in international prostate symptom score (IPSS) score was more significant in doxazosin group. Conclusion: Intranasal desmopressin, is an effective symptomatic treatment of men with BPH complaining of nocturia, as well as doxazosin treatment.